PENGARUH MEDIA TIGA DIMENSI TERHADAP HASIL BELAJAR BALOK DAN KUBUS SISWA KELAS V SD - Retno Dwi Sukmawati; Misdalina; Tanzimah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem in this research is the lack of use of varied media and methods resulting in low student mathematics learning outcomes. The purpose of this study was to determine whether there was any influence and use of three-dimensional media on student learning outcomes in mathematics subject matter of blocks and cubes for fifth grade elementary school students. This research method is a quantitative experiment with a true experimental design with a posttest-only control design. With the data collection technique using a test in the form of multiple choice questions. The population in this study were all fifth grade students at SD Negeri 106 OKU, taking samples with total sampling. Data analysis technique using test analysis Based on the results of the research that has been done, it can be concluded that there is a significant influence of three-dimensional media on the learning outcomes of block and cube material for fifth grade students of SD. Keywords: Three Dimensional Media, Learning Outcomes, net of blocks and cubes.